Catalytic asymmetric synthesis of a nitrogen heterocycle through stereocontrolled direct photoreaction from electronically excited state. Issue 1 (December 2017) - Huang, Xiaoqiang; Li, Xinyao; Xie, Xiulan; Harms, Klaus; Riedel, Radostan; Meggers, Eric
Abstract The reactivity of photoexcited molecules has been extensively studied for decades but until today direct bond-forming reactions of such excited states in a catalytic and asymmetric fashion are restricted to the synthesis of cyclobutanes via [2 + 2] photocycloadditions. Herein, we demonstrate a previously elusive visible-light-induced catalytic asymmetric [2 + 3] photocycloaddition of alkenes with vinyl azides. A wide range of complex 1-pyrrolines are obtained as single diastereoisomers and with up to >99% enantiomeric excess using a simple reaction setup and mild reaction conditions. The reaction is proposed to proceed through the photoexcitation of a complex out of chiral rhodium catalyst coordinated to α, β-unsaturatedN -acylpyrazole substrates. All reactive intermediates remain bound to the catalysts thereby providing a robust catalytic scheme (no exclusion of air necessary) with excellent stereocontrol. This work expands the scope of stereocontrolled bond-forming reactions of photoexcited intermediates by providing catalytic asymmetric access to a key nitrogen heterocycle in organic chemistry. Despite intensive research on photoexcited molecules, stereocontrol of direct bond formation upon photoexcitation remains limited. Here the authors expand the research on stereocontrolled bond forming photochemistry and introduce the catalytic asymmetric synthesis of chiral nitrogen heterocycles.